Video-feedback intervention (VIPP-SD) to promote maternal sensitivity in a Peruvian context of socioeconomic vulnerability - Retiz, Olenka (2025)
This study aims to describe clinical aspects that favored the efficacy of the 'Video-feedback intervention to promote positive parenting and sensitive discipline' (VIPP-SD) in a low SES dyad from Lima-Perú. The dyad consisted of a 37-year-old mother and her 17-month-old child living in a high-risk context. The intervention’s results on maternal sensitivity were measured using the Maternal Behaviour Q-Set 3.1. The mother went from a sensitivity score of -.53 before the intervention to .78 after it. This change’s statistical significance and clinical relevance was confirmed using the RCI indicator and the analysis of therapeutic change indicators proposed by Krause et al. (2006). The strategies used to strengthen the therapeutic alliance and maintain maternal commitment to the intervention are discussed.